2021
DOI: 10.3390/ph14010036
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib for Hepatocellular Carcinoma: A Literature Review

Abstract: Lenvatinib, which is an oral multikinase inhibitor, showed non-inferiority to the sorafenib in terms of overall survival (OS) and a higher objective response rate (ORR) and better progression-free survival (PFS) in patients with hepatocellular carcinoma (HCC). A good liver function and Barcelona Clinic Liver Cancer (BCLC) intermediate stage were the key factors in achieving therapeutic efficacy. The management of adverse events plays an important role in continuing lenvatinib treatment. While sequential therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 109 publications
(205 reference statements)
3
27
0
1
Order By: Relevance
“…Lenvatinib is an oral multitarget tyrosine kinase inhibitor (TKI) that has been demonstrated to exhibit potent antiangiogenic and tumor growth inhibitory activity in the treatment of a variety of solid tumors and approved as a monotherapy or combination therapy for differentiated thyroid, hepatocellular carcinoma, and renal cell carcinoma [18]. As a new first-line therapeutic agent in recent ten years, lenvatinib shows no inferior to sorafenib in overall survival (OS), progressive-free survival (PFS), and objective response rate (ORR) [10]. A recent open-label multicenter study showed that patients with unresectable HCC who responded to lenvatinib had a median overall survival time of 22 months [19].…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…Lenvatinib is an oral multitarget tyrosine kinase inhibitor (TKI) that has been demonstrated to exhibit potent antiangiogenic and tumor growth inhibitory activity in the treatment of a variety of solid tumors and approved as a monotherapy or combination therapy for differentiated thyroid, hepatocellular carcinoma, and renal cell carcinoma [18]. As a new first-line therapeutic agent in recent ten years, lenvatinib shows no inferior to sorafenib in overall survival (OS), progressive-free survival (PFS), and objective response rate (ORR) [10]. A recent open-label multicenter study showed that patients with unresectable HCC who responded to lenvatinib had a median overall survival time of 22 months [19].…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%
“…Despite mounting real-world evidence, there have been few reports of comprehensive findings on lenvatinib therapy for HCC. Meanwhile, some issues about pharmacological mechanisms included in HCC treatment by lenvatinib remain unresolved [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several newer agents have been established over the years, replacing sorafenib as the only systemic therapy available. Lenvatinib is another oral multikinase inhibitor proven to be non-inferior to sorafenib in terms of overall survival for patients with advanced HCC [ 68 ]. Lenvatinib has also showed statistically significant improvement in progression-free survival, objective response rate and time to progression [ 69 ].…”
Section: Combined Treatmentsmentioning
confidence: 99%
“…A recent study compared the median PFS in TACE-refractory patients that were treated with lenvatinib (5.8 months), sorafenib (3.2 months), and TACE (2.4 months). This indicates treatment with lenvatinib in replacement of TACE has the potential to acquire good therapeutic responses while preserving normal liver function (20). In terms of combination therapies, lenvatinib plus pembrolizumab (an anti-PD-1 antibody) showed encouraging results with improved ORR and DCR for unresectable HCC (NCT03006926, Table 2) (21).…”
Section: Lenvatinibmentioning
confidence: 99%